2017
DOI: 10.1063/1.4986224
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectrum of oscillations in generalized Sagdeev potential

Abstract: In this paper, the full energy spectrum of nonlinear oscillations, known as the cnoidal waves, is studied in the framework of small-amplitude Korteweg de Vries and modified Korteweg de Vries (mKdV) theories based on the pseudoparticle motion in Helmholtz and Duffing potentials by employing the newly introduced pseudoenergy concept. The pseudoenergy dependence of various cnoidal oscillation parameters is then studied, and it is shown that superposition of cnoidal waves leads to familiar beating and Lissajous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We observed that there are so many classes of NLEE arising in physics, fluid mechanics and engineering fields transferred to the following ODE: 3 0 αθ βθ γθ ′′ + + = (4) see [9,10,19,[22][23][24][25][26][27][28][29]31] and so on. This equation is often referred to the pseudoptential or sagdeev potential [30].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that there are so many classes of NLEE arising in physics, fluid mechanics and engineering fields transferred to the following ODE: 3 0 αθ βθ γθ ′′ + + = (4) see [9,10,19,[22][23][24][25][26][27][28][29]31] and so on. This equation is often referred to the pseudoptential or sagdeev potential [30].…”
Section: Introductionmentioning
confidence: 99%
“…The Jacobi-cn elliptic function has the limiting forms cn(x, 0)=cos(x) and cn(x, 1)=sech(x). Also, In the sinusoidal excitation limit we have Ψ 2 ;Ψ 3 , while in the soliton limit Ψ 1 ; Ψ 2 [68]. The weakly nonlinear driven excitations studied in this section may also be extended to the case with the hard wall rectangular potential well of length l similar to the case of linear excitations.…”
Section: Weakly Nonlinear Driven Excitationsmentioning
confidence: 90%
“…in which ¢ E is the energy eigenvalue of the plasma-phonon [68] and the pseudo-potential corresponding to this Hamiltonian reads…”
Section: Weakly Nonlinear Driven Excitationsmentioning
confidence: 99%
“…The later describes many interesting features of the nonlinear electrostatic waves in an electron-ion plasma such as energy spectrum, nonlinear resonance, harmonic generation, chaotic excitations and autoresonance effects which has been recently revisited in Refs. [32][33][34][35][36][37] using the recently developed pseudoparticle dynamics method. In the stationary frame ξ = x − Mt (M being the Mach number), the dissipationless hydrodynamic equations can be reduced to the following pseudoforce (Newton) equation of motion [38]…”
Section: Dynamics Of Hidden Particlesmentioning
confidence: 99%
“…The pseudoparticle formalism is particularly interesting because various collective excitations in a fluid even in the presence of dissipation [36] and external forcing effect can be described in terms of dynamics of a single particle-like motion in the generalized Sagdeev pseudopotential. In the small-amplitude weakly nonlinear potential limit of form V (φ) = −(c/2)Φ 2 + (d/3)Φ 3 or V (φ) = −(c/2)Φ 2 + (d/3)Φ 4 which are known as the Helmholtz and Duffing potentials, respectively, the energy equation ( 2) can be fully integrated to give Φ(ξ) in terms of Jacobielliptic functions [32]. The small-amplitude weakly nonlinear waves in a fluid are described by the celebrated Korteweg de Vries equation (KdVE) given as…”
Section: Dynamics Of Hidden Particlesmentioning
confidence: 99%